Implementasi Metode SMART dalam Sistem Pendukung Keputusan Pemilihan Pantai Terbaik - Marsono Marsono; Karina Andriani; Cindy Vivin Avilia; Evi Rosalina Widyayanti; Asyahri Hadi Nasyuha; Dedi Rahman Habibie (Bulletin of Computer Science Research, 2025)
Beaches in Bantul Regency, Yogyakarta, such as Parangtritis, Depok, Samas, Goa Cemara, and Baru Beaches, attract tourists for their natural beauty, recreational activities like sandboarding, and local traditions like the Labuhan ceremony. However, tourists struggle to find the best destination among the many beach options based on factors such as ticket price, distance from the city center, cleanliness, facilities, and culinary experiences. Using the Simple Multi-Attribute Rating Technique (SMART) method, this study aims to provide recommendations for the best beaches in Bantul. SMART is a method that offers an objective approach to overcome the limitations of subjective reviews on social media. Data were collected from 31 tourists through field observations and online questionnaires from August to September 2025 to assess the relevance of the criteria and the level of tourist satisfaction with the five beaches. Field observations examined facilities and cleanliness, and the questionnaire assessed tourist preferences using a Likert scale. Baru Beach was the best destination according to the SMART analysis with a score of 0.971, excelling in cleanliness and facilities. Followed by Goa Cemara Beach with a score of 0.968, Parangtritis with a score of 0.962, Depok with a score of 0.959, and Samas with a score of 0.916. These results help beach managers improve facilities and promotions, while also helping tourists choose beaches based on their preferences, such as affordability or appealing local cuisine. Furthermore, this research encourages coastal environmental conservation and increases tourist visits, driving local economic growth in Bantul.